The Party’S Cadre Political Training and Education in Vietnam – A Comparative Analysis with China - Anh, Dr. Nguyen Ngoc (RA Journal of Applied Research, 2021)
Following the system approach developed by David Easton (1967), this study aims to analyse the Party’s cadre training and development in Vietnam in comparison with China and test the hypothesis that the Party’s cadres training and development in Vietnam lags behind that in China, and there are good experience and lessons learnt in this process.The study shows that the cadre political training and education in Vietnam lags behind that in China in a number of ways: (i) lower quality, modernization and diversification of training programmes; (ii) less competitive and commercialized in cadre training; (iii) the political training and education in Vietnam is largely imposed on the learners, not selective and demand-driven like in China; (iv) remmunerations are more competitive in China for lecturers and speakers, including international ones. The implications for Vietnam include: (i) further improvement of the regulations and requirements on cadre training and development in Vietnam; (ii) renewing and updating training content, programme and methodology to make them more learner-oriented; (iii) enhancing quality of annual cadre training planning and delivery; (iv) adequate investment on physical facility for training institutions; (v) renewing the cadre training assessement; and (vi) further strengthening the research and international cooperation.